Rice water productivity mapping for Pindrawan Command Area using CROPWAT 8.0 Model and GIS - KUMAR, FANESH; SINHA, JITENDRA; JANGRE, NILIMA (Journal of Soil and Water Conservation, 2024)
Agriculture is the largest consumer of water and total evapotranspiration from global agricultural land could double in next 50 years if trends in food consumption and current practices of production continue. There is an immense need for enhancing per drop more crop. The present study focuses on assessment of rice water productivity for Pindrawan command area using CROPWAT 8.0 model and GIS. Twenty years meteorological data and crop coefficient (Kc) of rice at different crop growth stages were analyzed to estimate crop evapotranspiration (ETc). Production and productivity data of the study area were obtained from the Agriculture Department Government of Chhattisgarh. The results indicate that 20 years average crop water productivity (CWP) in the command area was found to be 0.59 kg m-3, varying from a minimum of 0.24 kg m-3 in the year 2017 to a maximum of 0.86 kg m-3in the year 2016. Average field water productivity (FWP, considering percolation losses) in the command area was found to be is 0.33 kg m-3, varying from a minimum of 0.14 kg m-3 in the year 2017 to a maximum of 0.49 kg m-3in the year 2016. Similarly, over the average of 20 years and 11 different villages in the study area, the maximum CWP was found as 0.595 kg m-3 in village Raikheda while the minimum was found as 0.564 kg m-3 in village Dhansuli. Maximum FWP was found as 0.341 kg m-3 in village Raikheda while the minimum was found as 0.323 kg m-3 in village Dhansuli. There is significant difference between CWP and FWP, this calls for urgent actions to reduce losses in the field.